37 Genetic aspects of livestock adaptation. (5th December 2019) - Riley, David G
Abstract: Livestock adaptation to less than favorable ambient has a genetic basis. Estimates of additive genetic variance and narrow sense heritability for % intramuscular fat in Hereford varied across United States geography quantifications evaluated in random regression analyses. Shedding and regrowth of winter coats of Angus cows in subtropical areas may indicate differential adaptation in cattle not adapted to the subtropics. Acquired adaptation to local conditions (multiple generations across more than 50 years) may was evidenced by performance of Florida Angus relative to prominent U.S. Angus in subtropical Florida; later sexual maturation may be a prominent component of such adaptation, and increasing milk production may be antagonistic to adaptation in natural conditions. Cattle temperament may be indicative of adaptation and is highly heritable; however, results from random regression analyses suggest that the additive genetic component appears to decrease in importance and the permanent environmental component of phenotype appears to become more important as calves age. Crossbreeding represents a proven strategy to improve adaptation almost immediately. Heterosis influences cattle body temperature maintenance, reproduction, survival, and, to a lesser extent, temperament in subtropical or other stressful environmental conditions (for example, in toxic fescue). Prenatal stress alters patterns of methylation (and likely other epigenetic mechanisms) and thereby encourages or inhibits gene expression to promote postnatal fitness. Brahman exposed to prenatal stress exhibited substantially different patterns of methylation across the genome in lymphocytes in both male and female calves; those patterns differed by sex. Female longevity may be the ultimate adaptation trait, as annual compliance to reproductive standards may be an appropriate assessment of a combination of attributes that represent adaptation. Longevity has documented heterotic influence; the additive genetic component is less well characterized but real. A simple, effective way to improve longevity may be to select bulls from aged, proven cows.